Sequential Cohort Analysis After Liver Transplantation Shows de Novo Extended Release Tacrolimus Is Safe, Efficacious, and Minimizes Renal Dysfunction - Lim, Tiong Yeng (Transplant Direct, 2020)
The use of once-daily extended-release tacrolimus (ERT) is associated with improved long-term graft and patient survival when compared with twice-daily tacrolimus (BDT), but the underlying reasons for differential survival are unclear. The aim of the study was to compare clinical outcomes known to impact on posttransplant survival for de novo BDT and ERT in liver transplantation (LT) recipients. METHODS. We conducted a single-center, prospective sequential cohort analysis of adult patients undergoing LT during a change in protocol from de novo BDT to ERT, with a 6-month post-LT follow-up. RESULTS. A total of 160 transplanted patients were evaluated; 82 were in the BDT group and 78 were in the ERT group. The cohorts were matched for standard variables and a similar proportion in each group received induction interleukin-2 receptor antibody (36% and 31%). There were no significant differences in the measured outcomes of patient and graft survival, biopsy-proven acute rejection episodes, post LT diabetes, and toxicity. A significantly lower number of patients developed chronic kidney disease Stage3–4 in the ERT cohort compared with BDT cohort. In patients with pre-LT renal dysfunction who received antibody induction, estimated glomerular filtration rate decreased significantly in the BDT but not the ERT group. CONCLUSIONS. We show that once-daily ERT is as safe and efficacious as BDT in de novo LT but optimally conserves renal function post-LT.